Multimedia Technologies in Education - Sobirovna, Valieva Hurmatoy; Muhiddinovna, Mahmudova Zulfiya; Yaxshinor qizi, Allayorova Noila (International Journal of Psychosocial Rehabilitation, 2020)
English language is very important nowadays. More and more people need English to attend universities and colleges, because now everybody have an opportunity to get higher education abroad. New ideas in science and medicine happen so quickly that it is impossible to translate everything into different languages. International relations are extended and strengthened through the exchange of scientific, technical, and cultural information. In this situation, foreign language teaching is a matter of state significance. Teachers of foreign languages make their contribution to all aspects of education of pupils. There are some useful principles and methods of teaching foreign languages. Their role in the upbringing of the younger generation cannot be overestimated. The interactive methods of foreign language teaching is not only new or mysterious, new techniques but also new forms, new principles, new approaches, new methods in teaching process. Interactive training encourages and gives learners to create comfortable condition of learning, also learners feel their successfulness, develop creativity, intellectual and communicative abilities.